CASE TICK-BORNE RICKETTSIAL DISEASE WITH LESIONS OF THE LUNGS - M. P. Onuhova; O. S. Litvinova; Ya. D. Yankovskaya; L. V. Sokolova; T. Ya. Chernobrovkina (Архивъ внутренней медицины)
In recent years, in Russia an average of 400 thousand people receives or medical aid after tick bite. The urgency of the problem of infections transmitted during tick bites is caused by the expansion of the range of ticks spread and increasing incidence of “tick” infections. Still clinical and laboratory diagnostics of tick-borne infections causes difficulties for doctors. The purpose of communication is to describe the clinical case of tickborne rickettsiosis with the development of specific community-acquired pneumonia.